Comparative analysis of splice form-specific expression of LIM Kinases during zebrafish development. - Ott, E; Te Velthuis, A; Bagowski, C (2007)
LIM Kinases (LIMK) are genes encoding multi-domain proteins that can contain up to two LIM domains, a single PDZ domain, and a tyrosine kinase domain. Alternative splicing is a source for different combinations of these domains. Two family members, LIMK1 and LIMK2 have been described in mammals and are important for organization of the actin cytoskeleton. We have cloned LIMK1 and LIMK2 from zebrafish and characterized their domain specific expression patterns during embryogenesis. The results on temporal and spatial expression of the LIM Kinases during embryogenesis indicate overlapping and distinct expression domains for LMK1 and LIMK2. Differences in expression during embryogenesis were observed for PDZ and LIM encoding splice forms for both LIM Kinases. To better understand the transcriptional regulation of LIM Kinases, we searched for conserved regulatory elements. We identified evolutionary conserved smad binding sites for LIMK2. In summary, we present here the splice-form specific temporal and spatial expression patterns for both LIMK1 and LIMK2 during zebrafish embryogenesis.